(untitled) - Vogel, G. Herbert (New Jersey, 2005)
Guiding readers through all steps of the complex process, this book covers the most diverse aspects of chemicals production, including those not or insufficiently covered in natural science courses. These comprise economic feasibility, patenting and licensing, demands on the location and the problem of waste disposal. Throughout, the author does not rely on simple references to other literature but instead reiterates many facts and places them in context, as well as succinctly explaining formulas, thus removing the need to look up items in secondary reference works. As such, the book is suitable for both newcomers as well as those already working in the field. Those working in R&D as well as plant managers will learn how to avoid pitfalls, resulting in higher safety. A common basis and indispensable ready reference for engineers and chemists.
Keywords: Chemical industries,Chemical engineering,Process equipment